2013
DOI: 10.1021/bi3010347
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Magnetic Resonance of CCCC RNA Reveals a Right-Handed Helix, and Revised Parameters for AMBER Force Field Torsions Improve Structural Predictions from Molecular Dynamics

Abstract: The sequence dependence of RNA energetics is important for predicting RNA structure. Hairpins with Cn loops are consistently less stable than hairpins with other loops, which suggests the structure of Cn regions could be unusual in the “unfolded” state. For example, previous nuclear magnetic resonance (NMR) evidence suggested that polycytidylic acid forms a left-handed helix. In this study, UV melting experiments show that the hairpin formed by r(5′GGACCCCCGUCC) is less stable than r(5′GGACUUUUGUCC). NMR spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
165
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(177 citation statements)
references
References 85 publications
12
165
0
Order By: Relevance
“…Together with CD and UV/Vis melting experiments, these data indicated that the ssRNA is in equilibrium between an ordered A-form-like helical conformation and a highly disordered partially melted state. Similar observations have since been made on polycytosine ssRNA sequences using NMR, UV melting, and MD simulations, showing that ssRNA order is not limited to polyadenine sequences (Tubbs et al 2013).…”
Section: Introductionsupporting
confidence: 76%
“…Together with CD and UV/Vis melting experiments, these data indicated that the ssRNA is in equilibrium between an ordered A-form-like helical conformation and a highly disordered partially melted state. Similar observations have since been made on polycytosine ssRNA sequences using NMR, UV melting, and MD simulations, showing that ssRNA order is not limited to polyadenine sequences (Tubbs et al 2013).…”
Section: Introductionsupporting
confidence: 76%
“…Interestingly, while we observe reactivity within the template, nucleotides 44-46 (CCC) consistently did not show reactivity above background levels, suggesting they may be stacked or involved in tertiary interactions. Polycytidylic acid alone can form a helix stabilized by base stacking or hydrogen bonding between adjacent bases (Arnott et al 1976;Freier et al 1981;Broido and Kearns 1982;Tubbs et al 2013). The CCC residues within the template could be adopting a similar structure, resulting in low NMIA reactivity.…”
Section: Resultsmentioning
confidence: 99%
“…Cytidine protonation would also change stacking interactions. A cytidine tetramer shows A-form stacking interactions by NMR (Tubbs et al 2013). If the cytidines were protonated, then different stacking interactions would likely form.…”
Section: Proposed Model For Predicting the Free Energies Of Asymmetrimentioning
confidence: 99%